Evaluating of Islamic Religious Education Curriculum Management Program at Madrasah Tsanawiyah in North Sumatera - Syafaruddin Syafaruddin; Edi Saputra; Sutrisno Sutrisno (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to obtain the evaluation results of the Islamic Religious Education curriculum management program at Madrasah Tsanawiyah in North Sumatra using the CIPP evaluation model (Context, Input, Process, and Product). This research is qualitative research with a management approach, and research data is obtained through participant observation, in-depth interviews, and documentation studies. In contrast, the data analysis uses descriptive analysis by reducing data, displaying data and drawing conclusions. The results show that in terms of context, the form of the Islamic Education curriculum used was based on the 2013 curriculum in the subjects of the Hadith Qur'an, Aqidah Akhlak, Fiqh, SKI, and three pesantren subjects, namely Arabic (Nahwu sorof), Calligraphy, and Takhfidzul Qur. Local curriculum-based is a basic need for schools, especially the community and students, in terms of input, the availability of adequate infrastructure, teacher qualifications according to scientific disciplines, although in terms of pedagogical competence, it is still not optimal in terms of process, program The Islamic Religious Education curriculum can be implemented well even though it is not optimal and sometimes there are still activities that are carried out, some are appropriate and some are not appropriate, in terms of product, the PAI curriculum provides a new direction that can build positive and negative civilizations both madrasas, teachers and student.